2018
DOI: 10.1093/geroni/igy014
|View full text |Cite|
|
Sign up to set email alerts
|

A Comprehensive Analysis of Morbidity Life Expectancies Among Older Hispanic Subgroups in the United States: Variation by Nativity and Country of Origin

Abstract: Background and ObjectivesAlthough a clear advantage in mortality has been documented among older Hispanic subgroups, particularly the foreign-born, research examining health selectivity in morbidity life expectancies among older Hispanics are scarce. Differences in sociocultural characteristics among Hispanic subgroups may influence racial/ethnic and nativity disparities in morbidity. Research examining the heterogeneity among older Hispanic subgroups may further our understanding of why some Hispanics are abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
(76 reference statements)
5
32
0
Order By: Relevance
“…This is supported by research in the Hispanic population in the United States that has found that the low mortality rate observed in Hispanics occurs in combination with a higher rate of disability, leading to a longer period of time spent disabled at the end of life [47]. There is also evidence 14 that some Hispanic subgroups have greater morbidity in later life compared to non-Hispanic whites [48].…”
Section: Discussionmentioning
confidence: 90%
“…This is supported by research in the Hispanic population in the United States that has found that the low mortality rate observed in Hispanics occurs in combination with a higher rate of disability, leading to a longer period of time spent disabled at the end of life [47]. There is also evidence 14 that some Hispanic subgroups have greater morbidity in later life compared to non-Hispanic whites [48].…”
Section: Discussionmentioning
confidence: 90%
“…This participant expressed feelings of being a minority within a minority (p. 519). Garcia, M., Garcia, C., Chiu, Raji, & Markides' (2018) study is reported to be "one of the first attempts in documenting the heterogeneity among older Hispanics by nativity, country of origin, and gender in life expectancies with morbidity and without morbidity" (p. 3).…”
Section: Introductionmentioning
confidence: 99%
“…Older Mexican Americans (25%) residing in the Southwestern United States are more likely to report depressive symptoms than other Hispanics (10.8%), non-Hispanic Blacks (8.9%), and non-Hispanic Whites (7.8%) at the national level (Black, Goodwin, & Markides, 1998;Dunlop, Song, Lyons, Manheim, & Chang, 2003). Lower mortality among older Mexican Americans (particularly the foreign-born) vis-à-vis non-Hispanic Whites, accompanied by a disproportionate burden of chronic disease, disability, and cognitive impairment suggests this population is at a greater risk of spending more years of late-life with depression (Fenelon, Chinn, & Anderson, 2017;Garcia, Garcia, & Ailshire, 2018;Garcia, Garcia, Chiu, Raji, & Markides, 2018;Hayward, Hummer, Chiu, González-González, & Wong, 2014), which has serious policy implications for quality of life, caregiver burden, and health care utilization among this rapidly growing population.…”
mentioning
confidence: 99%